The Impact of Monopoly on Uzbekistan’s Economy: A Case Study of UzAuto Motors - TOLIPOVA , Umida (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This thesis examines the impact of monopoly on the Uzbek economy with a specific focus on UzAuto Motors. It analyzes how monopolistic market structures influence pricing, competition, consumer welfare, and industrial development. Using secondary data and theoretical insights, the study highlights the economic consequences of sustained market dominance. The purpose of this research study is to investigate the effect that monopoly has had on the economy of Uzbekistan, with a particular emphasis on the case study of UzAuto Motors. The primary goals of this research were to determine the level of market concentration and monopolistic practises that are present in the automotive sector, investigate the impact that UzAuto Motors’ monopoly has had on market dynamics, pricing strategies, and consumer welfare, assess the impact that the monopoly has had on innovation, competitiveness, and the overall growth of the automotive industry, determine what regulatory measures and policy interventions can be implemented to lessen the negative effects of monopoly, and finally, present the findings and conclusions of the research. In order to accomplish these goals, a mixed-methods research strategy was utilised, which brought together quantitative and qualitative research strategies. Quantitative information was gathered by means of standardised questionnaires that were sent out to a variety of stakeholders, such as customers, professionals in the sector, and legislators. For the purpose of collecting information regarding market concentration, pricing tactics, consumer perceptions, and overall wellbeing, Likert scales and closed-ended questions were utilised. In-depth interviews were conducted with important industry experts, policymakers, and officials from UzAuto Motors, and open-ended questions were used to obtain qualitative data. The purpose of these interviews was to study the influence of the monopoly on innovation, competitiveness, and industry growth. The results of this research provided substantial new insights into the effects that the monopoly held by UzAuto Motors has had. According to the findings of the study, there is a significant positive association between high market concentration and low levels of competition. This finding draws attention to the monopolistic practises that are prevalent in the automobile industry. In addition, the regression analysis revealed a strong negative link between UzAuto Motors’ monopoly and the welfare of consumers, which suggests that consumers may be negatively impacted as a result of the absence of competition. The qualitative research found that UzAuto Motors’ dominant market position has inhibited innovation, with 75% of the interviewees expressing worries regarding the company’s lack of new and innovative car models. This was one of the main findings of the study. These findings indicate that the overall competitiveness and expansion of the automotive sector in Uzbekistan will suffer as a result of the influence that this has. Because of the ramifications of these findings, regulatory measures and policy actions are required to foster competition and reduce the detrimental effects of monopoly. The findings of this study contain a number of recommendations that can be utilised by policymakers, industry stakeholders, and UzAuto Motors to help create a more competitive market environment, improve market efficiency, and support the growth of the economy sustainably. This research paper focuses on the case study of UzAuto Motors in order to provide insightful information regarding the effect that monopoly has had on the economy of Uzbekistan. The findings shed light on the importance of taking action to reduce market concentration, encourage healthy competition, and improve the well-being of consumers. The supplied recommendations offer solutions for policymakers, industry stakeholders, and UzAuto Motors to build a more competitive market environment and support sustainable economic development in Uzbekistan. These tactics can be found in the provided recommendations.